Distinct functions of the laminin ? LN domain and collagen IV during cardiac extracellular matrix formation and stabilization of alary muscle attachments revealed by EMS mutagenesis in Drosophila. - Hollfelder, D.; Frasch, M.; Reim, I. (BMC Developmental Biology, 2014)
The Drosophila heart (dorsal vessel) is a relatively simple tubular organ that serves as a model for several aspects of cardiogenesis. Cardiac morphogenesis, proper heart function and stability require structural components whose identity and ways of assembly are only partially understood. Structural components are also needed to connect the myocardial tube with neighboring cells such as pericardial cells and specialized muscle fibers, the so-called alary muscles. Using an EMS mutagenesis screen for cardiac and muscular abnormalities in Drosophila embryos we obtained multiple mutants for two genetically interacting complementation groups that showed similar alary muscle and pericardial cell detachment phenotypes. The molecular lesions underlying these defects were identified as domain-specific point mutations in LamininB1 and Cg25C, encoding the extracellular matrix (ECM) components laminin ? and collagen IV ?1, respectively. Of particular interest within the LamininB1 group are certain hypomorphic mutants that feature prominent defects in cardiac morphogenesis and cardiac ECM layer formation, but in contrast to amorphic mutants, only mild defects in other tissues. All of these alleles carry clustered missense mutations in the laminin LN domain. The identified Cg25C mutants display weaker and largely temperature-sensitive phenotypes that result from glycine substitutions in different Gly-X-Y repeats of the triple helix-forming domain. While initial basement membrane assembly is not abolished in Cg25C mutants, incorporation of perlecan is impaired and intracellular accumulation of perlecan as well as the collagen IV ?2 chain is detected during late embryogenesis. Assembly of the cardiac ECM depends primarily on laminin, whereas collagen IV is needed for stabilization. Our data underscore the importance of a correctly assembled ECM particularly for the development of cardiac tissues and their lateral connections. The mutational analysis suggests that the ?6/?3/?8 interface of the laminin ? LN domain is highly critical for formation of contiguous cardiac ECM layers. Certain mutations in the collagen IV triple helix-forming domain may exert a semi-dominant effect leading to an overall weakening of ECM structures as well as intracellular accumulation of collagen and other molecules, thus paralleling observations made in other organisms and in connection with collagen-related diseases.